2017
DOI: 10.1097/brs.0000000000002254
|View full text |Cite
|
Sign up to set email alerts
|

Does Modic Change Progresss With Age?

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We detected Modic changes in 4.2% of patients and there was no gender predilection. Tarukado et al conducted a cross-sectional study regarding the prevalence of Modic changes in patients between the first and eighth decades of life [30]. They reported no patients with Modic changes at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…We detected Modic changes in 4.2% of patients and there was no gender predilection. Tarukado et al conducted a cross-sectional study regarding the prevalence of Modic changes in patients between the first and eighth decades of life [30]. They reported no patients with Modic changes at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed the role of vertebral BMF in lumbar disc degeneration and provides further evidence in the currently limited field. MRI quantitative and semi-quantitative studies have been conducted for patients with various ages with a primary focus on the variation of IVDD [29] or BMF [30], modic changes [31], and T2 and FF parameters studied separately with increasing age. To our knowledge, most studies have not reported the correlation of IVD T2 value and the Pfirrmann grading parameters with BMF in different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Modic changes are found in asymptomatic individuals and are to some degree dependent on age. The evidence for the presence of Modic changes as an association to low back pain is conflicting (11,(209)(210)(211)(212)(213)(214). Two reviews have found Modic type 1 changes to be relatively correlated to low back pain (211,212).…”
Section: Discussionmentioning
confidence: 99%